Sanitation and Hygiene Practice of Street Children Living in the Kathmandu Valley - Kunwar, Mala (Nepal Journal of Multidisciplinary Research, 2022)
Street children are spending the unhygienic life in street though they look happy to live in street. There is no exact data of street children in Nepal. Kathmandu is main city where more street children are seen begging in the street. The study was conducted to identify the sanitation and hygienic practice of street children living in the Kathmandu valley. There was total 234 street children selected for this study. The study found that majority of street children used to take path one time in every week. Similarly, majority of street children used the public toilet whereas 24% street children were using open space (open defecation) which was not good from the environmental perspective. The study also found that majority (58.12%) of street children used to take food from street shop. The food available in street shop is not hygienic because of the weak sanitation of surrounding environment. There is high chance of contamination due to dust pollution and use of untreated water for cooking food.